Endocardial and epicardial ECG imaging during sinus rhythm to detect local conduction delay in arrhythmogenic cardiomyopathy. (19th May 2022) - Boonstra, MJ; Te Riele, ASJM; Roudijk, RW; Kloosterman, M; Asselbergs, FW; Van Dam, PM; Loh, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Dutch Heart Foundation Introduction: We recently optimized our ECG imaging (ECGi) method for the estimation of endo- and epicardial activation during sinus rhythm. In patients with arrhythmogenic cardiomyopathy, late gadolinium enhancement (LGE)-CMR can identify regional myocardial injury and the combination of structural and electrical information may provide valuable insight in disease progression and risk stratification. However, the effect of structural disease and local conduction delay on the ECGi estimation of ventricular activation has not been studied. Purpose: Evaluate the relation between LGE-CMR and non-invasively estimated local conduction velocity (CV). Methods: 8 pathogenic mutation carriers (PKP2/PLN) underwent LGE-CMR for clinical follow up and 67 lead body surface mapping. Subject specific triangulated surface heart/torso/lung meshes were created. ECGi activation sequences were used to determine local CV with the triangulation method. The LGE location was identified according to the AHA 17 segment model. Per segment, variation in CV was computed and local activation timing maps and CV maps were constructed. Results: Isochronal crowding was observed in subjects in segments with LGE (figure, red boxes) and locally, conduction velocity decreased. Variation in conduction velocity per segment in subjects with extensive LGE presence (>9 segments) was higher 0.031±0.018 vs. 0.026±0.013 m/s/cm2 in subjects without. Conclusion: Our preliminary results indicate the ability of the ECGi method to identify regions with higher variation in local CV. This increase in CV variability might be used to assess the vulnerability to cardiac arrhythmia. Analysis will be extended towards the RV and subsequently, more subjects will be included.